2016
DOI: 10.1038/leu.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of CaMKIIγ accelerates chronic myeloid leukemia blast crisis

Abstract: Blast crisis (BC) is the final deadly phase of chronic myeloid leukemia (CML), but its molecular basis remains poorly understood. Here, we show that CML BC is regulated by calcium-calmodulin-dependent kinase IIγ (CaMKIIγ). Genetic deletion of CaMKIIγ greatly inhibits disease progression via selectively impairing the self-renewal of leukemia stem cells (LSCs) in mouse models, whereas overexpression of CaMKIIγ has the opposite effects. In human CML, phosphorylated CaMKIIγ abundance is significantly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…It is reported that BCR-ABL can elicit relocation of p27 kip1 marked by a reduced nucleus p27 kip1 by the activated AKT in the human CML CD34 þ cells, which facilitates cell cycling and expansion of CD34 þ pool (43). Consistently, reduced nucleus p27 kip1 caused by CaMKIIg-dependent phosphorylation of p27 kip1 at T187 can reactivate dormant LSCs in CML (44). In this sense, the increased nucleus p27 kip1 by MLN4924 may favor restriction of LSCs.…”
Section: Discussionmentioning
confidence: 84%
“…It is reported that BCR-ABL can elicit relocation of p27 kip1 marked by a reduced nucleus p27 kip1 by the activated AKT in the human CML CD34 þ cells, which facilitates cell cycling and expansion of CD34 þ pool (43). Consistently, reduced nucleus p27 kip1 caused by CaMKIIg-dependent phosphorylation of p27 kip1 at T187 can reactivate dormant LSCs in CML (44). In this sense, the increased nucleus p27 kip1 by MLN4924 may favor restriction of LSCs.…”
Section: Discussionmentioning
confidence: 84%
“…Many other genes are related to CML and stem cell maintenance and transformation. The tumor suppressor protein phosphatase 2A (PP2A) could reduce the survival and self‐renewal of LSCs through BCR‐ABL1 kinase‐independent and PP2A‐mediated inhibition of Jak2 and β‐catenin , whereas arachidonate 5‐lipoxygenase (5‐LOX) gene ( Alox5 ) and calcium‐calmodulin‐dependent protein kinase II (CaMKII), are critical regulators for LSCs in BCR‐ABL‐induced CML . Similarly, the tumor suppressor promyelocytic leukemia ( PML ) gene has been also identified as a regulator in the hematopoietic system and as an important controller for stem cell maintenance and differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…In the immune system, CaMKIIγ has influence on CD8 + T cell proliferation, immature T cell lifespan and T cell memory [ 25 , 26 ]. Our previous study and other data show that CaMKIIγ can regulate the proliferation and differentiation of AML [ 21 , 22 ], promote survival and self-renewal of leukemia stem cell and accelerate blast crisis of CML [ 23 , 24 ]. In this report, we define activated CaMKIIγ as an important regulator of T-ALL leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In myeloid leukemia cells, CaMKIIγ directly phosphorylates and enhances signal transducers and activators of transcription 3 (Stat3) transcriptional function [ 21 ]. Our previous study reveals that CaMKIIγ directly or indirectly phosphorylates the CDK inhibitor p27Kip1 and accelerates transition of both G 0 –G 1 and S–G 2 /M in cell cycles in CML cells [ 23 ]. We also observe that CaMKIIγ activates nuclear factor kappa B (NF-κB), β-catenin and Stat3 networks, which are essential for survival and self-renewal of LSC in CML cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation